Contribution of Eye-Foot Coordination, Agility, and Leg Length to Dribbling Ability in Football Games - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul; Saleh, M Sahib (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This research is a type of descriptive research that uses a "determination" research design. This study aims to determine; whether (1) if Is there a contribution of eye-foot coordination to the ability to dribble the ball in a soccer game; (2) Is there a contribution of agility to the ability to dribble the ball in football games; (3) Is there a contribution of leg length to the ability to dribble the ball in a soccer game; (4) Is there a joint contribution of eye-foot coordination, agility and leg length to the ability to dribble the ball in the game of football? The population is all students of SSB Syekh Yusuf Kab. Gowa. The sample used was 30 students. The sampling technique is random selection by lottery (Simple Random Sampling). The data analysis techniques used are descriptive analysis, regression analysis (r), and multiple regression analysis (R) at the significance level ? = 0.05. research results show that; (1) There is a contribution of eye-foot coordination to the ability to dribble the ball in football games, with a contribution value of 38.4% (P value < 0.05); (2) There is a contribution of agility to the ability to dribble the ball in the game of football, with a contribution value of 51.1% (P value < 0.05); (3) There is a contribution of leg length to the ability to dribble the ball in the game of football, with a contribution value of 21.6% (P value < 0.05); (4) There is a contribution of eye-foot coordination, agility and leg length to the ability to dribble the ball in the game of football, with a contribution value of 53.3% (P value < 0.05); and the calculated F value (F) is 9.896.